2023
DOI: 10.3389/fcimb.2023.1127369
|View full text |Cite
|
Sign up to set email alerts
|

Altered gut microbiota in the early stage of acute pancreatitis were related to the occurrence of acute respiratory distress syndrome

Abstract: BackgroundAcute respiratory distress syndrome (ARDS) is the most common cause of organ failure in acute pancreatitis (AP) patients, which associated with high mortality. Specific changes in the gut microbiota have been shown to influence progression of acute pancreatitis. We aimed to determine whether early alterations in the gut microbiota is related to and could predict ARDS occurrence in AP patients.MethodsIn this study, we performed 16S rRNA sequencing analysis in 65 AP patients and 20 healthy volunteers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…By affecting the microcirculation at the intestinal level, followed by a decrease in tissue perfusion, the integrity of the intestinal barrier is altered [ 29 ]. Numerous studies have demonstrated that intestinal permeability increases shortly after the onset of pancreatitis, a process followed by the translocation of bacteria to other locations ( Figure 1 ) [ 31 , 32 ].…”
Section: Gut Microbiota Profile In Pancreatitismentioning
confidence: 99%
See 4 more Smart Citations
“…By affecting the microcirculation at the intestinal level, followed by a decrease in tissue perfusion, the integrity of the intestinal barrier is altered [ 29 ]. Numerous studies have demonstrated that intestinal permeability increases shortly after the onset of pancreatitis, a process followed by the translocation of bacteria to other locations ( Figure 1 ) [ 31 , 32 ].…”
Section: Gut Microbiota Profile In Pancreatitismentioning
confidence: 99%
“…Selected studies ( Table 1 ) reported changes in the intestinal microbiota since the onset of acute pancreatitis, describing a decrease in bacterial diversity, with an increase at the phylum level in potentially pathogenic bacteria such as Bacteroidetes and Proteobacteria compared to healthy controls [ 32 , 37 , 38 , 39 , 40 ]. At the family level, Enterococcaceae , Enterobacteriaceae , and Bacteroidaceae increased, while at the genus level, Bacteroides , Enterococcus , and Escherichia–Shigella were more abundant in patients with AP [ 32 , 40 , 41 ].…”
Section: Gut Microbiota Profile In Pancreatitismentioning
confidence: 99%
See 3 more Smart Citations